Pengaruh Model Pembelajaran Aktif dengan Kartu Sortir terhadap Hasil Belajar Siswa SMA Swasta Nupela Tahun Pelajaran 2023/2024 - Novanolo Telaumbanua (Program Studi Pendidikan Biologi - Universitas Nias, 2024)
Low student participation and learning outcomes in Biology learning remain common problems in secondary schools, particularly because the learning process is still teacher-centered and does not actively engage students. This study aimed to analyze the effect of an active learning model using card sorting on students’ learning outcomes in biodiversity material at SMA Swasta Nupela in the 2023/2024 academic year. The study employed an experimental method with a randomized control-group pretest-posttest design. The research sample consisted of two classes: an experimental class taught using the active learning model with card sorting and a control class taught using conventional learning methods. Data were collected through multiple-choice learning outcome tests that had been validated and tested for reliability. The results showed that the average student learning outcome in the experimental class reached 83.18, categorized as good, while the control class obtained an average score of 75.76, categorized as sufficient. The hypothesis testing results indicated that the value of t count=2.628was greater than t table=1.988 at a significance level of 0.05. These findings demonstrated that the active learning model with card sorting had a significant effect on improving students’ Biology learning outcomes and was able to create a more interactive and meaningful learning environment.